2023
DOI: 10.1182/blood.2022019017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nirmatrelvir plus ritonavir treatment for patients with CLL during the Omicron Surge

Abstract: Patients with CLL, even in the omicron era and post-vaccination, suffer from persistent covid, higher complications and mortality compared to the general population. In the current study, we evaluated retrospectively the effectiveness of Nirmatrelvir plus ritonavir among 1,080 patients with CLL that were infected with SARS-CoV-2. Nirmatrelvir administration was associated with a reduction in Covid-19-related hospitalization or death by day 35. Specifically, the rate of Covid-19-related hospitalization or death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 17 publications
2
30
1
Order By: Relevance
“…All MBL patients achieved anti-spike levels ≥5000 AU/mL with three or more doses. In recent Israeli data, 27% received anti-viral therapy 14 and, similar to this study, all patients had nominally equal access. In our CLL cohort, 47.3% received anti-viral therapy and it did not affect the duration of COVID-19 (Figure S3).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…All MBL patients achieved anti-spike levels ≥5000 AU/mL with three or more doses. In recent Israeli data, 27% received anti-viral therapy 14 and, similar to this study, all patients had nominally equal access. In our CLL cohort, 47.3% received anti-viral therapy and it did not affect the duration of COVID-19 (Figure S3).…”
Section: Discussionsupporting
confidence: 83%
“…Second, the rates of hospitalisation and death are dramatically lower than in early waves prior to vaccine availability, and remain lower following vaccine availability than rates reported in North America and Europe in late 2022, 2,3,13 with many vulnerable CLL patients succumbing to COVID-19. These outcomes are also lower than those reported recently in the Omicron wave from Danish 4 and Israeli 14 data, and for the latter, comparable to the subgroup that received nirmatrelvir+ritonavir. Higher anti-spike antibody responses are associated with neutralising antibody and T-cell responses that are likely important components of protection against severe COVID-19.…”
Section: Discussioncontrasting
confidence: 74%
“…Accordingly, fewer patients needed hospitalization and ICU admission or died in the latter waves, despite that during these waves, more patients had comorbidities and/or were on active treatment at the time of COVID-19. This observation is likely related to the emergence of milder SARS-CoV-2 variants 8,35,36 and the significantly higher number of patients who received preemptive therapies in the latter waves but also the more effective therapies. Accordingly, infection during the four waves was an independent protective factor for hospitalization, but not for survival, since COVID-19 can still be severe and cause death in patients with CLL, irrespective of the SARS-CoV-2 variant (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HM, the EPICOVIDEHA SARS-CoV-2 infections registry demonstrated a significant reduction in mortality in 117 patients treated with Nirmatrelvir/ritonavir compared to 1,742 treated otherwise (2% vs. 11%, p = 0.036) [115]. Similarly, a retrospective registry study by Tadmor et al [116], which included 1,080 CLL patients infected with SARS-CoV-2, reported a significant reduction in hospitalization or death in CLL patients over the age of 65, who received Nirmatrelvir/ritonavir (4.8% vs. 10.2%; relative risk reduction 69%). It is important to consider contraindications and potential drug-drug interactions, which are common in patients with CLL.…”
Section: Post-exposure Prophylaxis Strategiesmentioning
confidence: 99%